An Innate Immunity-Regulating Virulence Determinant Is Uniquely Encoded within the Andes Virus Nucleocapsid Protein - Velasco Cimica (American Society for Microbiology, 2014)
ABSTRACT Andes virus (ANDV) is the only hantavirus known to spread from person to person and shown to cause highly lethal hantavirus pulmonary syndrome (HPS) in patients and Syrian hamsters. Hantaviruses replicate in human endothelial cells and accomplish this by restricting the early induction of beta interferon (IFN-β)- and IFN-stimulated genes (ISGs). Our studies reveal that the ANDV nucleocapsid (N) protein uniquely inhibits IFN signaling responses directed by cytoplasmic double-stranded RNA (dsRNA) sensors RIG-I and MDA5. In contrast, N proteins from Sin Nombre, New York-1, and Prospect Hill hantaviruses had no effect on RIG-I/MDA5-directed transcriptional responses from IFN-β-, IFN-stimulated response element (ISRE)-, or κB-containing promoters. Ablating a potential S-segment nonstructural open reading frame (ORF) (NSs) within the ANDV plasmid expressing N protein failed to alter IFN regulation by ANDV N protein. Further analysis demonstrated that expressing the ANDV N protein inhibited downstream IFN pathway activation directed by MAVS, TBK1, and IκB kinase ε (IKKε) but failed to inhibit transcriptional responses directed by constitutive expression of active interferon regulatory factor IRF3-5D or after stimulation by alpha interferon (IFN-α) or tumor necrosis factor alpha (TNF-α). Consistent with IFN pathway-specific regulation, the ANDV N protein inhibited TBK1-directed IRF3 phosphorylation (phosphorylation of serine 396 [pS396]) and TBK1 autophosphorylation (pS172). Collectively, these findings indicate that the ANDV N inhibits IFN signaling responses by interfering with TBK1 activation, upstream of IRF3 phosphorylation and NF-κB activation. Moreover, our findings reveal that ANDV uniquely carries a gene encoding a virulence determinant within its N protein that is capable of restricting ISG and IFN-β induction and provide a rationale for the novel pathogenesis and spread of ANDV. IMPORTANCE Andes virus (ANDV) is distinguished from other hantaviruses by its unique ability to spread from person to person and cause lethal hantavirus pulmonary syndrome (HPS)-like disease in Syrian hamsters. However, virulence determinants that distinguish ANDV from other pathogenic hantaviruses have yet to be defined. Here we reveal that ANDV uniquely contains a virulence determinant within its nucleocapsid (N) protein that potently inhibits innate cellular signaling pathways. This novel function of the N protein provides a new mechanism for hantaviruses to regulate interferon (IFN) and IFN-stimulated gene (ISG) induction that is likely to contribute to the enhanced ability of ANDV to replicate, spread, and cause disease. These findings differentiate ANDV from other HPS-causing hantaviruses and provide a potential target for viral attenuation that needs to be considered in vaccine development.